Trajectories of perinatal depressive symptoms in the context of the COVID‐19 pandemic. Issue 5 (27th August 2021) - Gustafsson, Hanna C.; Young, Anna S.; Doyle, Olivia; Nagel, Bonnie J.; Mackiewicz Seghete, Kristen; Nigg, Joel T.; Sullivan, Elinor L.; Graham, Alice M.
Abstract: This study sought to advance understanding of the potential long‐term consequences of the COVID‐19 pandemic for child development by characterizing trajectories of maternal perinatal depression, a common and significant risk factor for adverse child outcomes. Data came from 393 women (86% White, 8% Latina; mean age = 33.51 years) recruited during pregnancy ( n = 247; mean gestational age = 22.94 weeks) or during the first year postpartum ( n = 146; mean child age = 4.50 months; 55% female). Rates of depression appear elevated, relative to published reports and to a pre‐pandemic comparison group ( N = 155). This study also provides evidence for subgroups of individuals who differ in their depressive symptom trajectories over the perinatal period. Subgroup membership was related to differences in maternal social support, but not to child birth outcomes.